EFFECTIVENESS OF DRYING COAL POWDER IN OBTAINING ECO-QUALITY BRIQUETTES - Khakimov Akmaljon Akhmedovich; Vokhidova Nasiba Khabibullo qizi (American Journals Publishing, 2023)
In the process of obtaining the coal briquettes from the coal dust were analyzed the methods of maximum moisture loss in its composition. This was aimed at reducing the amount of toxic gases released during the combustion of briquettes for consumption.
Keywords: Coal composition, briquettes, sediment, anthracite, moisture, concentration, sulfur, exportable, drying drum, temperature, is gas.